(untitled) (Medical Forum Monthly, 2022)
Objective: Differentiated carcinomas of thyroid (DTC) are very common endocrine tumours with excellent prognosis and this study is aimed to highlight the presentation, management and outcome of the DTCs. Study Design: A retrospective study Place and Duration of Study: This study was conducted at the Surgical department of Khalifa Gul Nawaz Teaching Hospital Bannu in collaboration with the BINOR (Bannu Institute of Nuclear Medicine oncology and Radio-therapy situated in the vicinity of KGN MTI) from March 2014- March 2017 and was compiled in July 2021, after a follow up period of five years. Materials and Methods: A total of 300 patients of DTC, including 210 (70%) female and 90 (30%) male with nodular disease of thyroid (DTC) were included in this study. Age ranged from 18-85 years with a mean age of 45 years. Results: Out of the 300 patients with DTC, 190 were of papillary carcinoma, 90 with follicular carcinoma and 20 of mixed variety. 60 patients had lobectomy and out of these, 40 cases had completion thyroidectomy. 200 patients had total thyroidectomy and the remaining 40 cases having ipsilateral lymph nodes positive, had total thyroidectomy along with modified radical neck dissection. 130 (43%) patients had radioactive iodine therapy (in BINOR) 6-8 weeks after total thyroidectomy. 75 cases (25%) had regional and distant metastases. Altogether 7 patients died of the disease at the end of 5 years follow up. The mortality rate was 2.3%. Conclusion: Fine needle aspiration cytology (FNAC) is a gold standard, safe, inexpensive and reliable method of confirming the diagnosis of DTC. Management of DTC requires a multidisciplinary approach consisting of thyroid specialist surgeon, pathologist and specialist in radiation oncology and nuclear medicine. Surgery is the first line treatment while radioactive iodine therapy, TSH suppression, regular physical examination and imaging investigations like ultra-sound (US), CT scan and radioactive iodine scanning of the patients, periodic thyroglobulin detection are the good strategies regarding the management of the DTC.